BMI Modulates the Effect of Thyroid Hormone on Lipid Profile in Euthyroid Adults. (13th August 2017) - Wang, Yanqiu; Yin, Qinglei; Xu, Min; Ni, Qicheng; Wang, Weiqing; Wang, Qidi
Abstract : The impacts of thyroid hormones (TH) on lipid profile in euthyroid adults have gained much attention. It is currently unknown whether BMI influences such interaction. In the present study, we investigate the role of BMI in modulating the association between TH and lipid parameters in 1372 euthyroid healthy adults. Our results show that thyroid parameters are differentially associated with lipid profile. FT3 is positively correlated with total cholesterol (β = 0.176 ± 0.046, P < 0.001 ) and LDL cholesterol levels (β = 0.161 ± 0.040, P < 0.001 ). FT4 is negatively correlated with TG (β = − 0.087 ± 0.029, P < 0.01 ) while positively correlated with HDL cholesterol levels (β = 0.013 ± 0.005, P < 0.01 ). TSH is positively associated with TG (β = 0.145 ± 0.056, P < 0.05 ) and total cholesterol levels (β = 0.094 ± 0.030, P < 0.01 ). Importantly, BMI modulates the effect of TH on lipid profile: the interaction of FT4 and BMI and the interaction of FT3 and BMI reach statistical significance in predicting TG and HDL cholesterol levels, respectively. Stratified according to BMI levels, most associations between TH and lipid profile are significant only in normal-weight group. In conclusion, in euthyroid adults, high normal FT3, TSH levels, and low normal FT4 levels are associated with unfavorable lipid profile. BMI mediates the effect of thyroid function on lipid profile in euthyroid adults.